EFFECTS OF JONGI (Dillenia indica) LEAF EXTRACT IN RATS FED A HIGH-FAT DIET - Neysa Christabelin Quincy Bancin; Karyn Amelia Jane Widagdo; Maria Pingkan Putrika; Aliyya Clarisa Maharani; Afuza Ahnaf Dzulfikar; Oktavia Rahayu Adianingsih (Meditory : The Journal of Medical Laboratory, 2026)
Background: Obesity is a complex metabolic disorder associated with various health risks, including cardiovascular disease, diabetes, and hepatic steatosis. Given the limitations of current pharmacological treatments, there is increasing interest in natural products with anti-obesity potential, such as jongi (Dillenia indica). Objective: This study evaluated the effects of Dillenia indica leaf extract in rats fed a high-fat diet. Methods: Thirty male Wistar rats were divided into five groups: standard diet, high-fat diet, and three others receiving high-fat diets (HFD) supplemented with either 500 mg/kg or 750 mg/kg of Dillenia indica extract, or 10 mg/kg of orlistat. HFD was administered to the corresponding groups for 28 days, followed by oral treatment for 14 days. Parameters measured included body weight, liver weight, lipid profiles, and adipocyte area. Results: The group treated with 750 mg/kg of Dillenia indica showed numerically lower liver weight, total cholesterol, LDL, and triglyceride levels compared with the HFD group. However, these differences were not statistically significant. Both Dillenia indica treatment groups showed significantly lower mean adipocyte areas than the HFD group (p < 0.05), with the lowest mean area observed at 750 mg/kg BW. Conclusions: Dillenia indica leaf extract at a dose of 750 mg/kg BW significantly reduced adipocyte area in HFD-fed rats. However, its effects on body weight, liver weight, and lipid profiles were not statistically significant. Further long-term studies with a broader range of doses are required.